PENGARUH MODAL SOSIAL TERHADAP KESIAPSIAGAAN BENCANA DI KAWASAN PESISIR PANTAI AIR MANIS KOTA PADANG - husnul ramadhan; M. Fachri Adnan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Abstract This research is writen to know the positive relation between social capital and preperadnes disaster. The independent variabel used in this research is modal sosial and dependen variabel is preperadnes disaster. The subject in this research is civiel society at the Air Manis coast. Method of collecting data that is used in this research is quitioner with likert scale. All of the data that the authour get is analyzed by statiscal SPSS 17.0. quantitative data is analized by product moment analisis technique. The result show that there is positive realtion between social capital and preperadnes disaster in civiel society at the Air Manis coast. The result of data analisis corelation coefficient is 59.3%. That mean is have positive relation between social capital and preperadnes disaster. Wich higher the social capital of civiel society is higher preperadnes disaster. It also mean that the lower social capital of civiel society is lower preperadnes disaster. Key word: social capital, preperadnes disaster